Phase field modeling using petiGA - Vignal, P.; Collier, N.; Calo, Victor (2013)
Phase field modeling has become a widely used framework in the computational material science community. Its ability to model different problems by defining appropriate phase field parameters and relating it to a free energy functional makes it highly versatile. Thermodynamically consistent partial differential equations can then be generated by assuming dissipative dynamics, and setting up the problem as one of minimizing this free energy. The equations are nonetheless challenging to solve, and having a highly efficient and parallel framework to solve them is necessary. In this work, a brief review on phase field models is given, followed by a short analysis of the Phase Field Crystal Model solved with Isogeometric Analysis using PetIGA. We end with an introduction to a new modeling concept, where free energy functions are built with a periodic equilibrium structure in mind. © 2013 The Authors. Published by Elsevier B.V.